2020
DOI: 10.3390/en13092327
|View full text |Cite
|
Sign up to set email alerts
|

A Modelica Toolbox for the Simulation of Borehole Thermal Energy Storage Systems

Abstract: Borehole thermal energy storage (BTES) systems facilitate the subsurface seasonal storage of thermal energy on district heating scales. These systems’ performances are strongly dependent on operational conditions like temperature levels or hydraulic circuitry. Preliminary numerical system simulations improve comprehension of the storage performance and its interdependencies with other system components, but require both accurate and computationally efficient models. This study presents a toolbox for the simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…[29] Later, the earliest method of producing nanofibrous materials from polymer solutions was patented by Anton Formhals in 1934. [30] Between 1964 and 1969, Geoffrey Taylor, appertaining to Zeleny's work, mathematically demonstrated that the critical half-angle of the meniscus nears 49.3°at the furthest point before the disintegration event, illustrating why a polymer solution or melt extruded through a capillary will reshape from a spherical to a conical configuration in a strong electric field. [31,32] This gave rise to the concept of the "Taylor cone" formation.…”
Section: Brief Historymentioning
confidence: 99%
“…[29] Later, the earliest method of producing nanofibrous materials from polymer solutions was patented by Anton Formhals in 1934. [30] Between 1964 and 1969, Geoffrey Taylor, appertaining to Zeleny's work, mathematically demonstrated that the critical half-angle of the meniscus nears 49.3°at the furthest point before the disintegration event, illustrating why a polymer solution or melt extruded through a capillary will reshape from a spherical to a conical configuration in a strong electric field. [31,32] This gave rise to the concept of the "Taylor cone" formation.…”
Section: Brief Historymentioning
confidence: 99%
“…[101] Copyright 2021, Wiley-VCH. the 1900s, greater advances have been achieved, with patents describing a prototype of the setup for electrospinning by John Cooley [106] and William Morton, [107] followed by a few years later with the patents by Anton Formhals [108,109] disclosing the improvement in equipment, moving toward the commercialization of electrospinning for the fabrication of textile yarns, or finally with the pioneering work by Geoffrey Taylor between 1964 and 1969 describing the formation of Taylor cone. [110][111][112] This technology is relatively versatile and easy to operate, allowing the production of continuous and long fibers with diameters ranging from micrometers to nanometers, implemented in many industrial companies nowadays.…”
Section: Electrospinningmentioning
confidence: 99%
“…Electrospinning, first introduced by Formhals in 1934, has been widely adopted as an effective and versatile technique to produce fibers with diameters ranging from nano- to micrometers. , A large variety of synthetic and natural polymers have been electrospun to form nanofiber systems used in fields such as tissue engineering, protective clothing, , environmental protection, , sensors, optics, and water filtration and purification . The wide applicability of such nanofibrous nonwoven materials is largely due to the remarkable properties of the nanofiber systems, including a high surface area-to-volume ratio, tunable porosity, and the ability to manipulate the nanofiber composition to acquire the desired properties and function …”
Section: Introductionmentioning
confidence: 99%